Tiridates in the Forum, Peroz on His Knees: Religion and Reputation in Ancient Iranian Diplomacy - Nabel, Jake (Anabasis. Studia Classica et Orientalia, 2019)
In 66 CE, the Arsacid dynast Tiridates bowed before Nero in the Roman forum in order to “receive” the kingdom of Armenia from the emperor. The scholarly literature on this episode, though large, has done little to reconstruct the Arsacid view of the coronation. This article decenters the Roman perspective through a reading of the day’s events anchored in Zoroastrianism. Taking a later anecdote about the Sasanian king Peroz as a point of departure, the discussion surveys Zoroastrian beliefs and practices concerning the sun, morning prayer, and Mithras, all of which featured in Tiridates’ investiture. Where previous treatments have seen Tiridates’ prostration before Nero as either a humiliating self-abasement or an intercultural religious collaboration, it is argued here that the Arsacid may have construed the proceedings as a routine Zoroastrian rite – an interpretation that could have preserved his dignity and circumvented Rome’s hegemonic ascription of meaning to this high-profile diplomatic affair.